(untitled) (Bangladesh Rice Journal, 2021)
Nutrient management influences soil health and crop productivity. Sustained crop production re-quires specific nutrient management options after a certain period. The objectives of this investigation were to examine the effects of inorganic and organic fertilization on yields and soil carbon budget under rice based cropping patterns in Bangladesh. The research data and informationhave been gen-erated based on previouslypublished, unpublished sources and own concept.Omission of K or im-balanced K are more influential for reduction in grain yield up to 47% in Boro (dry) season but N was most limiting up to 35% in T. Aman (wet) season. With existing fertilizer rates for growing rice, the balances of N and K are always negative. Balanced chemical fertilizer (NPKSZn) can be an option for improving crop productivity and maintain soil quality. Net ecosystem carbon (C) balances are posi-tive when 3 t ha-1 cow dung (CD), 2 t ha-1 poultry manure (PM) and 2 t ha-1 vermicompost (VC) are used in combination with chemical fertilizers. Soil amendments with organic nutrient sources (rice straw, CD, PM, VC, legume crops) and rice based cropping patterns such as T. Aman-Mustard-Boro, Boro-Fallow-Fallow, Jute-T. Aman-Fallow, Wheat-Mungbean-T. Aman, Grass pea- T. Aus-T. Aman and Potato-Boro-T. Aman can be beneficial in improving soil C budget, soil nutrient ratio, total crop production and maintenance of environmental health that will meet SDGs goal. Bangladesh Rice J. 24 (2): 119-131, 2021